An overview of molecular biology and nanotechnology based analytical methods for the detection of SARS-CoV-2: promising biotools for the rapid diagnosis of COVID-19. Issue 5 (5th February 2021) - Kailasa, Suresh Kumar; Mehta, Vaibhavkumar N.; Koduru, Janardhan Reddy; Basu, Hirakendu; Singhal, Rakesh Kumar; Murthy, Z. V. P.; Park, Tae-Jung
Abstract : Molecular biology and nanotechnology based analytical methods have proven to be promising diagnostic tools for the rapid diagnosis of COVID-19. Abstract : Currently, the 2019 novel coronavirus (2019-nCoV) is drastically affecting 214 countries, causing severe pneumonia in patients, which has resulted in lockdown being implemented in several countries to stop its local transmission. Considering this, the rapid screening and accurate detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; 2019-nCoV) play an essential role in the diagnosis of COVID-19, which can minimize local transmission and prevent an epidemic. Due to this public health emergency, the development of ultra-fast reliable diagnostic kits is essential for the diagnosis of COVID-19. Recently, molecular biology and nanotechnology based analytical methods have proven to be promising diagnostic tools for the rapid screening of 2019-nCoV with high accuracy and precision. The main aim of this review is to provide a retrospective overview on the molecular biology tools (reverse transcription polymerase chain reaction (RT-PCR) and reverse transcription loop-mediated isothermal amplification (RT-LAMP)) and nanotechnology based analytical tools (enzyme-linked immunosorbent assay (ELISA), RT-PCR, and lateral flow assay) for the rapid diagnosis of COVID-19. This review also presents recent reports on other analytical techniques including paper spray mass spectrometry for the diagnosis of COVID-19 in clinical samples. Finally, we provide a quick reference on molecular biology and nanotechnology based analytical tools for COVID-19 diagnosis in clinical samples.